Sex-Specific Survival, Growth, Immunity and Organ Development in Preterm Pigs as Models for Immature Newborns - Bæk, Ole; Cilieborg, Malene Skovsted; Nguyen, Duc Ninh; Bering, Stine Brandt; Thymann, Thomas; Sangild, Per Torp (Frontiers in Pediatrics, 2021)
Background. After very preterm birth, male infants show higher mortality than females, with higher incidence of lung immaturity, neurological deficits, infections and growth failure. In modern pig production, piglets dying in the perinatal period (up to 20%) often show signs of immature organs, but sex-specific effects are not clear. Using preterm pigs as model for immature infants and piglets, we hypothesized that neonatal survival and initial growth and immune development depends on sex. Methods. Using data from a series of previous intervention trials with similar delivery and rearing procedures, we established three cohorts of preterm pigs (90% gestation), reared for 5, 9 or 19 days before sample collection (total n=1938 piglets from 109 litters). Partly overlapping endpoints among experiments allowed for multiple comparisons between males and females for data on mortality, body and organ growth, gut, immunity and brain function. Results. Within the first two days, males showed higher mortality than females (18 vs. 8%, P<0.001), but less severe immune response to gram-positive infection. No effect of sex was observed for thermoregulation or plasma cortisol. Later, infection resistance did not differ between sexes, but growth rate was reduced for body (up to -40%) and kidneys (-6%) in males, with higher leucocyte counts (+15%) and lower CD4 T cell fraction (-5%) on day 9 and lower monocyte counts (-18%, day 19, all P<0.05). Gut structure, function and necrotizing enterocolitis (NEC) incidence were similar between groups, but intestinal weight (-3%) and brush-border enzyme activities were reduced at day 5 (lactase, DPP IV, -8%) in males. Remaining values for blood biochemistry, haematology, bone density, regional brain weights and visual memory (tested in a T maze) were similar. Conclusion. Following preterm birth, male pigs show higher mortality and slower growth than females, despite limited differences in organ growth, gut, immune and brain functions. Neonatal intensive care procedures may be particularly important for compromised newborns of the male sex. Preterm pigs can serve as good models to study the interactions of sex- and maturation-specific survival and physiological adaptation in mammals.